Analisis Organizational Citizenship Behavior (OCB) Pada Generasi Z Karyawan PT. X - Safitri, Rika; Wiradendi Wolor, Christian; Marsofiyati (Teewan Journal Solutions, 2025)
Every company expects optimal performance from all of its employees to support the achievement of the company's main objectives. Therefore, it is important for the company to consider factors that can affect performance, one of which is employee behavior that contributes positively to the work environment. This study aims to describe the level of Organizational Citizenship Behavior (OCB) among Generation Z employees at PT. X. OCB reflects extra-role behaviors that go beyond formal duties and contribute to the success and smooth operation of the company. Using a qualitative approach, this research collected data from four key informants through in-depth interviews and direct observation in the work environment. The findings indicate that Generation Z employees at PT. X tend to demonstrate good altruism behavior, where they voluntarily assist colleagues in need without expecting rewards. In addition, they also show high civic virtue by actively participating in various company activities aimed at the progress of the organization. However, there are some challenges that the company must address, such as limited receptiveness to criticism. This may impact the overall improvement of OCB.